2012
DOI: 10.1016/j.jtcvs.2011.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anterior strut chordal transection on the force distribution on the marginal chordae of the mitral valve

Abstract: BACKGROUND Transection of the secondary chordae on the anterior leaflet of the mitral valve to relieve leaflet tethering and reduce regurgitation is an experimentally proven procedure to correct functional mitral regurgitation. In this study, we sought to investigate if transecting the secondary chordae has an impact on the marginal chordal force on the same leaflet. METHODS Adult porcine mitral valves (N =8) were studied in a pulsatile heart simulator, in which the papillary muscle positions can be precisel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…1a). 5,8,12,[18][19][20]22,23,[26][27][28][29][30][31][32][34][35][36][37][38][39]44,[46][47][48] These components are supplemented by systemic resistances and compliances to control cardiac output, systemic pressures, and dampen undesired flow and pressure oscillations within the rigid chambers of the system.…”
Section: Characteristics Of Pulsatile and Static Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…1a). 5,8,12,[18][19][20]22,23,[26][27][28][29][30][31][32][34][35][36][37][38][39]44,[46][47][48] These components are supplemented by systemic resistances and compliances to control cardiac output, systemic pressures, and dampen undesired flow and pressure oscillations within the rigid chambers of the system.…”
Section: Characteristics Of Pulsatile and Static Modelsmentioning
confidence: 99%
“…While the majority of annuluses reported in literature provide only a single size, adjustable and flexible annuluses have been reported. 22,29,37,46,47 These designs are described and evaluated in subsequent sections evaluating methods of assessing MV annuloplasty.…”
Section: Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Padala et al 19 have recently assessed the effects of secondary chordal cutting on marginal (primary) chordae in a pulsatile left heart simulator. These investigators found an increase in marginal chordal force when apical tethering was induced, with no further adverse effect of secondary chordal cutting.…”
mentioning
confidence: 99%
“…However, division of secondary chords led to an increased force on marginal chords when the leaflets were tethered in an apical-lateral direction, with an even more pronounced effect during apical-lateral-posterior tethering. 19 What effect such increased forces on the marginal chords may have on ventricular function is currently unknown, but it is important to note that the marginal chord force levels did not reach those required to induce chordal rupture.…”
mentioning
confidence: 99%